Heritagisation, re-heritagisation and de-heritagisation of built environments : The urban transformation of Kiruna, Sweden - Sjöholm, Jennie (Luleå tekniska universitet, Arkitektur och vatten, 2016)
This doctoral thesis presents research that aimed to contribute to the understanding of heritagisation in built environments and how heritagisation interacts with structural changes to an environment. The theoretical framework of the research was based on heritagisation, a concept defined by Harrison (2013) as the process through which objects, places and practices are turned into cultural heritage. The research was part of a single case study investigating conceptualisations of built heritage during the urban transformation of the town of Kiruna. Kiruna is a mining town in the northernmost part of Sweden that has plans to be relocated so that the mining company LKAB can continue mining the iron ore deposit that extends underneath the settlement. Kiruna is also a designated heritage site since the 1980s, and includes a large number of protected buildings. Hence, it is of interest how the built heritage is managed during the urban planning process. This is not only because the urban planning situation, which includes the relocation of an entire town, is special, but also because the town’s built heritage inevitably will change during the urban transformation. The research underlying this thesis has followed heritagisation during the urban transformation, from 2004, when the urban transformation was announced, until 2015. The empirical data used consist of planning documents, media reporting and observations, which together provide an overall view of the public discussions over the course of the urban planning process. Findings from the Kiruna case study show that the town’s officially recognised built heritage corresponds with the concept of an authorised heritage discourse (AHD). This heritage discourse was challenged by the urban transformation. Conservation goals are not clearly stated in the urban planning process and there are differing ideas for how to manage historic buildings during the urban transformation. These ideas shift both over time and between stakeholders, and the outcome of the urban planning ...